Sleeve-Shaped Neurothekeoma of the Ulnar Nerve: A Unique Case of a Still Unclear Pathological Entity. (January 2020) - Vetrano, Ignazio G.; Levi, Vincenzo; Pollo, Bianca; Chiapparini, Luisa; Messina, Giuseppe; Nazzi, Vittoria
Background: Neurothekeomas are slow-growing, well-circumscribed benign neoplasms. They usually involve cutaneous or subcutaneous tissues. Although originally described as myxomas deriving from nerve sheath cells, their exact histological classification is still uncertain. Peripheral nerve localization is rarely reported. Here, we describe a unique case of sleeve-shaped neurothekeoma of the ulnar nerve, which was incidentally discovered during a cubital tunnel release surgery.Methods: A 57-year-old man was admitted at our institution with clinical, ultrasonographic, and electromyographic findings highly suggestive of cubital tunnel syndrome. During ulnar nerve decompression surgery, however, no bony or ligament compression was noticed, but a segment of the nerve wrapped by a thick sleeve-shaped tissue, which had no clear-cut cleavage plane from the nerve. Given this unexpected finding, the en bloc excision of the lesion was avoided. A nerve decompression with biopsy of the swelling portion of the lesion was performed instead.Results: Histological examination described abundant myxoid stroma, with epithelioid and ring-shaped cells arranged in cords, negative to S100 protein at immunohistochemical analysis. This pattern was suggestive of neurothekeoma. The patient showed improvement in hypermyotrophy and intrinsic weakness of the hand.Conclusions: To the best of our knowledge, this is the first report of a sleeve-shaped neurothekeoma of the ulnar nerve. The exact pathological characterization of such rare entities remains uncertain. In case of peripheral nerve localization, and when a clear cleavage plane is absent, the correct management of these lesions should be that of simple nerve decompression followed by biopsy.